An Overview of Tools to Score Severity in Pediatric Inflammatory Bowel Disease - Shaoul, Ron; Day, Andrew S. (Frontiers in Pediatrics, 2021)
The management of IBD entails the use of various treatments (nutrition, medications and surgery) in order to induce and maintain remission. The assessment of IBD disease activity is based on a combination of symptoms, clinical findings, imaging and endoscopies. As in any disease, reliable assessment of disease activity or severity is required in order to plan relevant follow-up, decide on appropriate investigations, determine the best treatment option and subsequently assess response to treatment. It is extremely important for proper documentation, follow-up, assessment of response to treatment and communication, especially in patients with IBD, to talk the same language by using validated and widely used scores for disease activity, endoscopic and radiologic activity and patient reported outcomes both for clinical practice and research. This review aims to highlight key tools available for the assessment of disease activity or severity in individuals (especially children) with IBD. Methods: The authors performed a literature search using MEDLINE, Pubmed, and the Cochrane Library with the last search date of August 2020. Since evidence-based reports on several aspects of IBD scoring in children are limited we have included data from adults as well. Conclusions: The adaptation of scoring to the pediatric IBD population should allow us to improve patient care and outcome.